Cultural Criticism: Term, Concept, References - Al Shorofat, Abdallah Ayed (Journal of Humanities & Social Sciences, 2021)
This study aims at exploring the field of cultural studies and mainly the field of cultural criticism, which depends on the intertwined formats and postmodern methodologies, and that start from studying the theme as an organic unit in this new knowledge orientation, with the introduction of basic concepts that determine its path- i. e. cultural criticism, the idiomatic and its references on which it is based. This study seeks to identify the theoretical background for this critical approach, and the conceptual root of the cultural system. Consequently, the study will produce the descriptive approach with a historical tendency in order to present a vision that reflects cultural criticism in a concept and a term, and stands on the most important milestones in its course, starting with the reference frameworks that paved the way for its emergence until its appearance as one of the new errata cal trends in Western criticism. The importance of the study lies in its endeavor, in combination with other similar studies, to fill the special gaps in the concept of cultural criticism in a way that removes the ambiguity and ambiguity among many Arab scholars. This is what makes the call for more studies that reveal it, at the levels of theory and practice, and bring it closer to the Arab recipient as a legitimate and necessary matter.
Keywords: cultural studies; cultural criticism; format; postmodernism